PENGEMBANGAN E-MODUL BERBANTUAN MEDIA CAI PADA MATA PELAJARAN FOTOGRAFI KELAS X DESAIN KOMUNIKASI VISUAL DI SMK NEGERI 1 SUKASADA - Ariasa, Komang; Santyadiputra, Gede Saindra; Sindu, I Gede Partha (Jurnal Pendidikan Teknologi dan Kejuruan, 2017)
The purposes of this study were (1) to generate a design and implement the result of the design for the development of e-modul assisted CAI media on the subject of photography for tenth grade of Desain Komunikasi Visual at SMK Negeri 1 Sukasada, (2) to know the responses of the teacher and students toward development of e-modul assisted CAI media on the subject of photography for tenth grade of Desain Komunikasi Visual at SMK Negeri 1 Sukasada. The learning model that used in the development of electronic modul was project based learning. The type of research used in this study was the Research and Development (R&D) using ADDIE development model. The subjects of this study were tenth grade students of Desain Komunikasi Visual at SMK Negeri 1 Sukasada in academic year 2016/2017. In order to know the response of the teacher and students of e-module photography, questionnaire was used to obtain the data. The results showed that: (1) The design and implementation of e-module assisted CAI media which have been developed on the photography course for tenth grade of Desain Komunikasi Visual at SMK Negeri 1 Sukasada was successfully applied by some of the tests conducted. (2) The results of the data analysis showed that the mean score obtained from teacher’s responses was 47, if it converted into a table of classification response; it was classified as the category of very positive. Meanwhile, the mean score obtained from the students' response of the development of e-module, was 67,79, if it converted into a table of classification response, student responses classified as category of very positive.Keywords: E-Module, Photography, Project Based Learning